Synaptic vesicle release regulates pre-myelinating oligodendrocyte-axon interactions in a neuron subtype-specific manner - Gronseth, James R.; Nelson, Heather N.; Johnson, Taylor L.; Mallon, Taryn A.; Martell, Madeline R.; Pfaffenbach, Katrina A.; Duxbury, Bailey B.; Henke, John T.; Treichel, Anthony J.; Hines, Jacob H. (Frontiers in Cellular Neuroscience, 2024)
Oligodendrocyte-lineage cells are central nervous system (CNS) glia that perform multiple functions including the selective myelination of some but not all axons. During myelination, synaptic vesicle release from axons promotes sheath stabilization and growth on a subset of neuron subtypes. In comparison, it is unknown if pre-myelinating oligodendrocyte process extensions selectively interact with specific neural circuits or axon subtypes, and whether the formation and stabilization of these neuron-glia interactions involves synaptic vesicle release. In this study, we used fluorescent reporters in the larval zebrafish model to track pre-myelinating oligodendrocyte process extensions interacting with spinal axons utilizing in vivo imaging. Monitoring motile oligodendrocyte processes and their interactions with individually labeled axons revealed that synaptic vesicle release regulates the behavior of subsets of process extensions. Specifically, blocking synaptic vesicle release decreased the longevity of oligodendrocyte process extensions interacting with reticulospinal axons. Furthermore, blocking synaptic vesicle release increased the frequency that new interactions formed and retracted. In contrast, tracking the movements of all process extensions of singly-labeled oligodendrocytes revealed that synaptic vesicle release does not regulate overall process motility or exploratory behavior. Blocking synaptic vesicle release influenced the density of oligodendrocyte process extensions interacting with reticulospinal and serotonergic axons, but not commissural interneuron or dopaminergic axons. Taken together, these data indicate that alterations to synaptic vesicle release cause changes to oligodendrocyte-axon interactions that are neuron subtype specific.